Mediating Effect of Capital Expenditure on the Effect of Revenues, Allocation Fund, and Tax/Nontax Sharing on Economic Growth (Empirical Study of Regencies in Bengkulu Province Period of 2009-2015) - Elsivera Elsivera; Willy Abdillah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This research examines the mediating effect of capital expenditure on the relationship between regional revenues (PAD), general allocation fund (DAU), specific allocation fund (DAK), and tax sharing fund/non tax sharing (DBH) on the economic growth. Secondary data were collected from 10 regencies in Bengkulu Province for the period of 2009 to 2015. This research used panel data analysis. The results showed that capital expenditure did not mediate the relationship between regional generated revenues, general allocation fund, specific allocation fund, and tax sharing fund/non tax sharing to economic growth. Meanwhile, general allocation fund have positif effect on economic growth. Regional generated revenues and specific allocation fund have negative effect on economic growth, regional revenues and specific allocation fund also have positive effect on capital expenditure. Implication for stakeholders and further research are discussed. Keywords: Capital Expenditure, Economic Growth, General Allocation Fund, Regional Generated Revenues, , Specific Allocation Fund, Tax Sharing Fund /Non Tax Sharing